CHRONIC RHINITIS WITH BACTERIAL SECONDARY INFECTION IN A LOCAL CAT - Arya Duta Adnyana; Sri Kayati Widyastuti; I Nyoman Suartha (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
Rhinitis is an upper respiratory tract disorder in cats that involves irritation and inflammation of the nasal mucosa. Cats suffering from rhinitis may exhibit various clinical signs, such as sneezing, coughing, fever, respiratory distress (either in the form of rapid or slow breathing), nasal discharge, hypersalivation, excessive tearing, and lymph node swelling. This article aims to identify the results of anamnesis, clinical signs, and supporting examination findings in a feline case to determine the diagnosis and evaluate the provided therapy. The case subject is a 6-year-old cat named Kumeng, weighing 3.4 kg, with a tabby coat and local breed. The cat has been experiencing symptoms such as sneezing, nasal discharge, and difficulty breathing for the past five months. Physical examination revealed nasal discharge. Supporting examination findings, such as X-rays, showed no changes in the lower respiratory tract but nasal examination show increased opacity, and hematological results were normal. However, bacterial isolation from the nasal discharge identified the presence of four bacteria: Staphylococcus sp., Bacillus sp., Proteus sp., and Micrococcus sp. Cytological examination of the discharge also showed the presence of inflammatory neutrophil cells. The treatment provided included doxycycline hyclate at 10 mg/kg body weight q24h for 14 days, the anti-inflammatory methylprednisolone at 0.5 mg/kg body weight q24h for 7 days, the mucolytic bromhexine HCl at 1 mg/kg body weight q24h, and a multivitamin tablet q24h. On the 14th day after treatment, the frequency of sneezing in the cat was reduced, and the nasal discharge became more watery and clear.